Criticism in public sphere: the press development in Iran's civil society 1997-2000 - Zoeram, Vahid Amani; Lee, Yok Fee (Canadian Center of Science and Education, 2010)
From 1997 to 2000 Iran witnessed a flourishing evolution in the printed media. Reformists’ main agenda on civil society predisposed appropriate conditions for the expanding of press in Iran, both in quantity and quality characteristics. This article examines some important changes on the press to show how the press helped to develop critical public sphere in Iran during that time. Research outcomes show that many of the political and intellectual debates that considered as taboos and were not to be discussed at once, were changed to public issues and were criticized by the press in the public sphere of Iran’s society, and this was a great advantage for the Iran's civil society.